Perdagangan Bebas (Free Trade) dalam Perspektif Keadilan Internasional - Suherman, Ade Maman (UI Scholars Hub, 2008)
International trade law is to serve as an effective vehicle for the development of a truly global social and economic policy. As is seems destined to do, there must be a clearly articulated normative framework for the analysis of international trade law as a matter of justice. Due to that argument, international trade law can not be separated from international legal system which should be built under the construction of justice theory, that heavily influenced by the development of utilitarian, libertarian, international trade law should be based on the efalitarian theory that advocared by Rawls.